Penggunaan Aplikasi Anates pada Analisis Butir Soal Penilaian Tengah Semester Bahasa Indonesia Kelas X MIPA 8 SMA Muhammadiyah 2 Surabaya - Rufi’I I; Fibrina Aquatika Aquatika; Moch. Hendy Bayu Pratama (Metalanguage: Jurnal Ilmu Bahasa dan Sastra Indonesia, 2022)
In this study, we will discuss quantitative descriptive research which aims to determine the quality and feasibility of the mid-semester assessment items for class X MIPA 8 at SMA Muhammadiyah 2 Surabaya. The quality and feasibility of the items can be seen from the validity, reliability, level of difficulty, discriminatory power, and quality of distractors. The research subjects were 30 students of class X MIPA 8. The data was collected through the distribution of Mid-Semester Assessment questions filled out by students, then processed using Anates ver. 4.0.9. The test results show that the items are quite feasible to be tested but still need improvement. This is because there are still some questions with poor quality